Electrospun PLA Fibers Containing Metronidazole for Periodontal Disease - Budai-Szűcs M; Léber A; Cui L; Józó M; Vályi P; Burián K; Kirschweng B; Csányi E; Pukánszky B (Dove Medical Press, 2020)
Mária Budai-Szűcs, 1 Attila Léber, 1 Lu Cui, 2, 3 Muriel Józó, 2, 3 Péter Vályi, 4 Katalin Burián, 5 Balázs Kirschweng, 2, 3 Erzsébet Csányi, 1 Béla Pukánszky 2, 3 1Institute of Pharmaceutical Technology and Regulatory Affairs, Faculty of Pharmacy, University of Szeged, Szeged, Hungary; 2Laboratory of Plastics and Rubber Technology, Department of Physical Chemistry and Materials Science, Budapest University of Technology and Economics, Budapest H-1521, Hungary; 3Institute of Materials and Environmental Chemistry, Research Centre for Natural Sciences, Hungarian Academy of Sciences, Budapest H-1519, Hungary; 4Department of Periodontology, Faculty of Dentistry, University of Szeged, Szeged, Hungary; 5Institute of Clinical Microbiology, Faculty of Medicine, University of Szeged, Szeged, HungaryCorrespondence: Mária Budai-SzűcsInstitute of Pharmaceutical Technology and Regulatory Affairs, Faculty of Pharmacy, University of Szeged, Eötvös utca 6, Szeged 6720, HungaryTel +36 62 545-573Fax +36 62 545-571Email maria.szucs@pharm.u-szeged.huPurpose: Electrospun PLA fiber devices were investigated in the form of fiber mats and disks. Metronidazole was used as an active agent; its concentration was 12.2 and 25.7 wt% in the devices.Methods: The structure was studied by X-ray diffraction and scanning electron microscopy, drug release by dissolution measurements, while the antimicrobial efficiency was tested on five bacterial strains.Results: The XRD study showed that the polymer was partially crystalline in both devices, but a part of metronidazole precipitated and was in the form of crystals among and within the fibers. Liquid penetration and dissolution were different in the two devices, they were faster in disks and slower in fiber mats, due to the morphology of the device and the action of capillary forces. Disks released the drug much faster than fiber mats. Although the release study indicated fast drug dissolution, the concentration achieved a plateau value in 24 hrs for the disks; the inhibition effect lasted much longer, 13 days for bacteria sensitive to metronidazole. The longer inhibition period could be explained by the slower diffusion of metronidazole located inside the fibers of the device.Conclusion: The results suggest that the devices may be effective in the treatment of periodontitis.Keywords: drug release devices, fiber mats, disks, morphology, dissolution, capillary forces, diffusion, antimicrobial, inhibition